Measuring Equity in Health Care Financing : Reflections on (and Alternatives to) the World Health Organization's Fairness of Financing Index - Wagstaff, Adam (World Bank, Washington, DC, 2014)
In its latest World Health Report, The World Health Organization (WHO) argues that a key dimension of a health system's performance is the fairness of its financing system. The report discusses how policymakers can improve this aspect of performance, proposes an index of fairness, discusses how it should be put into operation, and presents a league table of countries, ranked by fairness with which their health services are financed. The author shows that the WHO index cannot discriminate between health financing systems that are regressive, and those that are progressive - and cannot discriminate between horizontal inequity, and progressiveness, or regressiveness. The index cannot tell policymakers whether it deviates from 1 (complete fairness) because households with similar incomes spend different amounts on health care (horizontal inequity), or because households with different incomes spend different proportions of their income on health care (vertical inequity, given the WHO's interpretation of the ability-to-pay principle) - although the two have different policy implications. With the WHO's index, progressiveness, and regressiveness are both treated as unfair. This makes no sense, because policymakers who may be strongly averse to regressive payments (which worsen income distribution) may in the name of fairness be quite receptive to progressive payments (requiring that the better-off, who may be willing to spend proportionately more on health care, are required to pay proportionately more). The author compares the WHO index with an alternative, and more illuminating approach developed in the income redistribution literature in the early 1990s, and used in the late 1990s, to study the fairness of various OECD health care financing systems. He illustrates the differences between the approaches with an empirical comparison, using data on out-of-pocket payments for health services in Vietnam for 1993 and 1998. This analysis is of some interest in its own right, given the large share of health spending from out-of-pocket payments in Vietnam, and the changes in fees, and drug prices over the 1990s.